The Role of Humus NGO in Children Empowerment Streets in the East Bekasi Project Market Area - Andri Prakarsa (The International Journal of Politics and Sociology Research, 2022)
The number of street children is currently increasing, especially in the Bekasi area, many street children in search of economic needs, become buskers, beggars, scavengers, hawkers. The government has regulations on the fate of child laborers, but the government has not been able to handle the problem of street children. Therefore, it is necessary to have a synergy between the government and the community as well as NGOs in solving the problems of street children. Seeing the increasing problem of street children, for this reason, the participation of the community and NGOs is expected to reduce the number of street children through empowerment programs for street children, then what is the role of the HUMUS NGO in empowering street children in the Pasar Project area of ​​East Bekasi programs in the empowerment of street children, how street children respond to empowerment, and what are the supporting and inhibiting factors in the empowerment program. In empowering the HUMUS NGO, it runs educational programs, such as early childhood education (PAUD), tutoring, equivalence education packages A, B, and C, religious education, formal school scholarships, child and family counseling, and the arts. The results of this study indicate that the HUMUS NGO provides empowerment in the form of educational programs such as early childhood education (PAUD), tutoring, equivalence education packages A, B, and C, religious education, formal school scholarships, child and family counseling, and art. The response from street children is quite good in accepting the program and the response from parents and the community is quite good in supporting the existence of the HUMUS NGO in running the program. There are also supporting factors, such as the motivation of street children to learn, the existence of educators to teach, adequate facilities, and support from the surrounding community. As for the inhibiting factors in carrying out each activity program, such as funding or finance, the mental attitude of street children who are accustomed to being on the road so it is difficult to manage, social workers who come in and out, and the traditions of the local community who are poor.